Pendalaman Teori Mazhab Kognitivistik dalam Pembelajaran Bahasa Arab - Hana Zafira Zahra S; Brian Prilliano; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2025)
This study discusses cognitive theory as one of the major schools in educational psychology and its implications for Arabic language learning. Cognitive theory emerged as a response to the limitations of behaviorism, emphasizing that learning is an internal process involving mental activities such as thinking, understanding, and problem-solving. Key figures such as Jean Piaget, Jerome Bruner, and Lev Vygotsky made significant contributions to the development of this theory through the concepts of cognitive development, discovery learning, and social interaction in learning. This study also integrates information processing and constructivism approaches as further developments of the cognitive school. The relevance of this theory to Arabic language learning lies in the need for active learning strategies, the use of symbolic and visual media, and the strengthening of social interaction in the language acquisition process. The discussion is supported by reflection on the Qur’anic verse QS. Al-‘Alaq: 1–5, which emphasizes the importance of reading, writing, and building knowledge gradually. This study concludes that the cognitive approach supports more meaningful, active, and contextual Arabic language learning.